Electronic and photophysical properties of 2-(2′-hydroxyphenyl)benzoxazole and its derivatives enhancing in the excited-state intramolecular proton transfer processes: A TD-DFT study on substitution effect - Rathawat Daengngern (2018)
© 2015 Elsevier B.V. Allrightsreserved. The effect of electron donating and withdrawing substituents on the enol absorption and keto emission spectra of 2-(2′-hydroxyphenyl)benzoxazole (HBO) and its derivatives has been systematically investigated by means of density functional theory (DFT) and time-dependent DFT (TD-DFT) methods. The enol absorption spectra of HBO were simulated by using five different DFTs with various exchange-correlation functions to validate a suitable functional prior to being further used as a method of choice to study the effect of substituents on the spectral characteristics of HBO derivatives. The popular B3LYP (Becke, three-parameter, Lee-Yang-Parr) exchange-correlation functional is found to provide the best desirable result in predicting the absorption spectrum close to experimental data. In the ground state, enol forms of HBO and its derivatives are more stable than those of keto forms, while in the first lowest excited state, keto forms are found to be more stable than their enol forms. Overall, simulated absorption and emission spectra of HBO and its derivatives from TD-B3LYP calculations are in good agreement with the experimental data. For enol, absorption maxima of HBO derivatives having electron-withdrawing groups are red-shift corresponding to their lower HOMO-LUMO energy gaps compared to that of HBO. For keto emission, HBO having electron donating groups (m-MeHBO and MHBO) and withdrawing group (CNHBO) at 4′-position on the phenol fragment as well as electron donating groups (HBOMe and HBOM) at 6-position on the benzoxazole fragment make the position of keto emission peak shift to shorter wavelength (blue-shift). However, HBO derivatives with electron withdrawing groups (HBOF, HBOCl, HBOA and HBOE) at 6-position give redshifted emission compared to the parent compound (HBO). The type of substituent on both 4′- and 6-positions certainly has a pronounced effect on the absorption and emission spectra of HBO derivatives.